Microstructure and characterizations of portland-bottom ash-silica fume cement pastes - Wongkeo W. (2014)
This research investigated the microstructure and characterization of Portland-bottom ash-silica fume cement pastes. Bottom ash, a by - product from coal-fired thermal power plants, was obtained from Mae Moh power plant, Lampang, Thailand. It currently exists as waste approximately 1.5 MT per year and has not been put to use. Unlike its counterpart, fly ash, which is recognized as an alternative material used to replace part of Portland cement. Silica fume, a nanomaterial from ferrosilicon industry, is nanoparticle and highly amorphous. It is highly pozzolanic reaction and could improve properties of Portland-bottom ash cement pastes. Thus, this research investigated the effect of silica fume on microstructure and characterization of Portlandbottom ash-silica fume cement pastes. The ratios of bottom ash used to replace Portland cement were 0, 10, 20 and 30 percent by weight and silica fume was added at 5 and 10 percent by weight. Compressive strength test was then carried out. SEM and TGA were used to study the microstructure of Portland-bottom ash-silica fume cement pastes. The results show that, the compressive strength of Portland-Bottom ash-silica fume cement pastes increased with added silica fume at 5 and 10 percent. SEM micrographs show C-S-H gel and silica fume around the cement particle in Portland-bottom ash-silica fume cement pastes which gives a highly dense and less porous microstructure. TGA graphs show Ca(OH)2 decreased with silica fume content. © 2008 Trans Tech Publications, Switzerland.